2022
DOI: 10.3390/plants12010025
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic and Natriuretic Effects of Hesperidin, a Flavanone Glycoside, in Female and Male Hypertensive Rats

Abstract: Hesperidin (HSP) is a major flavanone glycoside in citrus fruits, including sweet oranges and lemons. It demonstrates numerous pharmacological activities, such as antihypertensive effects and cardiac and kidney tissue protection. However, its effect on modulating renal function has yet to be properly explored. Female and male Wistar spontaneously hypertensive rats (SHR) were used to test the effect of HSP on renal function. The rats were divided into different groups, treated orally, and placed in metabolic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…For the diuresis assay, the animals were individually placed in individual metabolic cages, and the urine volume was collected over a 6-h period. The volume was calculated in relation to body weight and expressed as mL/100 g [ 21 , 44 , 45 , 46 ]. Electrolyte excretion (Na + , K + , Ca 2+ , and Cl − ), pH, conductivity, creatinine, urea, and glucose were measured in each urine sample at the end of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…For the diuresis assay, the animals were individually placed in individual metabolic cages, and the urine volume was collected over a 6-h period. The volume was calculated in relation to body weight and expressed as mL/100 g [ 21 , 44 , 45 , 46 ]. Electrolyte excretion (Na + , K + , Ca 2+ , and Cl − ), pH, conductivity, creatinine, urea, and glucose were measured in each urine sample at the end of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Souza et al (2023) showed the diuretic action of hesperidin, a flavanone glycoside from Citrus fruits, in hypertensive rats. The authors suggested that the activity is associated with the cholinergic pathway [14].…”
mentioning
confidence: 99%